The Relationship Between Personality Traits, Resilience, School Support, and Creative Teaching in Higher School Physical Education Teachers - Deng, Qian; Zheng, Bing; Chen, Jing (Frontiers in Psychology, 2020)
The investigation has been carried out on the status quo of higher school physical education teachers’ personality traits, resilience, and their creative teaching status. The exploratory and confirmatory factor analysis, combined with multiple stratified linear regression analysis, were used to verify the data obtained by the structure model. The results show that: 1) big five personality traits，except conscientiousness, the rest of four dimensions personality traits have different influences on creative teaching; 2) extraversion, agreeableness, and openness can produce an intermediary effect on innovative teaching through different dimensions of resilience; 3) the school support has a positive influence on five aspects of the creative teaching; 4) problem cognition and empathy in resilience play a multilevel role of mediating effect and are regulated variables as well. The findings of the present study revealed that the key to success to creative teaching is to understand teachers’ personality traits, pay attention to the resilience of the development of teachers’ creative teaching, and provide required support; the higher the awareness of the problem and the degree of school support in the resilience was, the higher the problem solving and the higher degree of teaching in the creative teaching tended to be.